PRIORITAS PROGRAM PENGEMBANGAN KETERAMPILAN PETANI PADI LADANG DI KECAMATAN SUNGAI LAUR KABUPATEN KETAPANG - Dewi Kurniati; Severianus Bito Palar; Maswadi (JURNAL BORNEO AKCAYA, 2022)
This study aims to determine the priority of the skill development program for upland rice farmers. This research was conducted in July – August 2021 and is located in Sungai Laur District, Ketapang Regency. The method used in this study is a qualitative descriptive method. The sampling technique used was purposive sampling. The sample used consisted of farmer group leaders, agricultural extension workers, the Department of Agriculture, Livestock and Plantation (Distanakbun) of Ketapang Regency. Data collection was done by observation, interviews, and distributing questionnaires. The data analysis technique used the Analytical Hierarchy Process (AHP) model with the help of Expert Choice 11 software. The respondents were 16 farmers, the head of the farmer group, 2 agricultural extension workers, and the Head of Agricultural Extension from the Distanakbun Ketapang Regency. This study resulted that the mechanized/modern land management program was a priority program for developing the skills of upland rice farmers in Sungai Laur District.